Reading Between The Shadows: Barthes' Semiotic Analysis of 'The Monstrumologist' Cover Design - Hendratno, Hendratno (Institut Seni Indonesia Padang Panjang, 2024)
The book cover design plays a crucial role in attracting readers' attention and conveying the essence of the story within. This article analyzes the cover of